PREVALENSI KASUS KEMATIAN AKIBAT HIV-AIDS PADA INSTALASI FORENSIK RSUD DR. M. HAULUSSY AMBON TAHUN 2015-2017 - Azatil Ishmah Matdoan; Costantinus W. Sialana; Johan B. Bension (PAMERI, 2019)
HIV is one of many communicable diseases that has major role of many number of deaths in the world. The cause of the death is not from HIV itself but from opportunistic infections caused by AIDS. The aim of this study is to describe the prevalence of death cases due to HIV/AIDS in forensic department of RSUD Dr. M. Haulussy Ambon year 2015-2017. This study is a descriptive study by collecting data from patient registry book in forensic department of RSUD Dr. M. Haulussy Ambon year 2015-2017. Collected samples are 3.337 samples and 203 of them are HIV/AIDS-related deaths. The results of this study are described by using pie charts and tables . The results show that the prevalence of death cases due to HIV/AIDS in forensic department of RSUD Dr. M. Haulussy Ambon tend to increase each year, from 2015 (46 deaths), 2016 (67 deaths), until 2017 (90 deaths). Men are most likely to die because of HIV/AIDS compared to women with 137 number of deaths. The highest number of deaths due to HIV/AIDS occur among group age from 15 to 49 years old with 183 deaths. Patients that died because of HIV/AIDS mostly lived in Ambon city compared to the other regions in Molucca with 148 deaths.